Synthesis of glycopoly(pseudo amino acid)s and their interaction with lectins - Lee, Ren-Shen; Peng, Kang-Yu (Reactive & functional polymers, 2012)
In this study, we developed a novel bioeliminable amphiphilic glycopoly(pseudo amino acid), which was synthesized by the condensation polymerization of N-benzyloxycarbonyl-4-hydroxyl-l-proline (NZHpr) followed by the coupling of an alkynyl-functional sugar derivative to the azido-end group, P(NZHpr)n. The glycosylated P(NZHpr)n polymers formed micelles in the aqueous phase. Selective lectin binding experiments confirmed that the glycosylated P(NZHpr)n can be used in biorecognition applications. The DOX-loaded micelles facilitated improved uptake of DOX by HeLa cells within 2h and were primarily retained in the cytoplasm, whereas free DOX tended to accumulate in the nuclei. The DOX-loaded glucosylated P(NZHpr)n micelles exhibited a substantially lower cytotoxicity compared to free DOX.